Law and protestantism the legal teachings of the Lutheran Reformation - Witte, John 1959- (Cambridge University Press, 2002)
The Lutheran Reformation of the early sixteenth century brought about immense and far-reaching change in the structures of both church and state, and in both religious and secular ideas. This book investigates the relationship between the law and religious ideology in Luther's Germany, showing how they developed in response to the momentum of Lutheran teachings and influence. Profound changes in the areas of education, politics and marriage were to have long-lasting effects on the Protestant world, inscribed in the legal systems inherited from that period. John Witte, Jr. argues that it is not enough to understand the Reformation either in theological or in legal terms alone but that a perspective is required which takes proper account of both. His book should be essential reading for scholars and students of church history, legal history, Reformation history, and in adjacent areas such as theology, ethics, the law, and history of ideas